FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA SEKTOR INDUSTRI HEALTHCARE DI INDONESIA - Ramadhaningsih, Devi; Indrati, Menik (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to investigate the impact of capital structure, company size, sales growth, and managerial ownership on profitability. In this study, the capital structure variable is measured by Debt to Equity Ratio (DER), company size is measured by the natural logarithm (Ln) of Total Assets, and sales growth is measured by the difference in the level of sales obtained this year minus the level of sales obtained last year divided by the level of sales last year, and managerial ownership is measured by the number of shares owned by management divided by the number of shares outstanding. This study uses the purposive sampling technique with the multiple linear regression analysis method using the Statistical Program for Social Science 25 (SPSS) application. The research population includes healthcare sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period, with 33 companies. The results of this study indicate that capital structure has a negative effect on profitability, company size has a negative effect on profitability, sales growth has a positive effect on profitability, managerial ownership has a positive effect on profitability, and profitability is measured by Return on Assets (ROA). Keywords: Capital Structure; Company Size; Sales Growth; Managerial Ownership; Profitability